The Effect Of Core Stability Exercise To Improve Leg Muscle Strength And Performance Men's Volleyball Athletes Age 18-25 In Surakarta - Anantyo Raharjo, Fadjar, Isnaini Herawati, S. Fis, M.Sc (2016)
Background: In the sport of volleyball athlete must also have a physical condition and a good performance. Additionally leg power needed to do jump smash, block, as well as service. Core Stability Exercise plays an important role in lower extremity the stabilization and the transfer of energy from the lower extremities to the body. One of the exercises that can be done is exercise to increase leg muscle strength and performance. Objective: To determine the effect of Core Stability Exercise to improve leg muscle strength and performance men's volleyball athletes age 18-25 in Surakarta. Methods: This study is a quasi experimental with pre and post test with control group design with a number of samples is 16 samples. Measuring instrument used is the Vertical Jump Test and One Minute Sit Up Test. Data were analyzed using wilcoxon test to test the influence. Results: There is Core Stability Exercise to improve leg muscle strength mens's volleyball athletes are the results obtained z value -3.520 p value (asymp sig) 0.000. There is Core Stability Exercise to improve performance mens's volleyball athletes are the results obtained z value -3.533 p value (Asymp sig) 0.000. Sig < 0,05. Conclusion: The Effect of Core Stability Exercise with a frequency of 3 times a week for 1 month was shown to significantly influence the effect of Core Stability Exercise to improve leg muscle strength and performance men's volleyball athletes age 18-25 in Surakarta.